2022
DOI: 10.3802/jgo.2022.33.e66
|View full text |Cite
|
Sign up to set email alerts
|

The added value of SLN mapping with indocyanine green in low- and intermediate-risk endometrial cancer management: a systematic review and meta-analysis

Abstract: Objective The aim of this study was to assess the SLN detection rate in presumed early stage, low- and intermediate-risk endometrial cancers, the incidence of SLN metastases, and the negative predictive value of SLN mapping performed with indocyanine green (ICG). Methods A systematic review with meta-analyses was conducted. Study inclusion criteria were A) low- and intermediate-risk endometrial cancer, B) the use of ICG per cervical injection; C) a minimum of twenty inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 41 publications
4
13
0
Order By: Relevance
“…Thus, only one patient who received an injection of ICG presented a true false‐negative result: a 58‐year‐old woman with grade 2 endometrioid cancer was diagnosed with positive lymphovascular space invasion and deep myometrial involvement. As reported before, the sensitivity of SLN mapping with ICG ranged from 77.8% to 100%, and the NPV ranged from 96.6% to 100% 25,32,40,41 . The NPV of ICG in our study was comparable, whereas the sensitivity was relatively low, which may be the result of the lack of performance of the ultrastaging procedure.…”
Section: Discussionsupporting
confidence: 74%
“…Thus, only one patient who received an injection of ICG presented a true false‐negative result: a 58‐year‐old woman with grade 2 endometrioid cancer was diagnosed with positive lymphovascular space invasion and deep myometrial involvement. As reported before, the sensitivity of SLN mapping with ICG ranged from 77.8% to 100%, and the NPV ranged from 96.6% to 100% 25,32,40,41 . The NPV of ICG in our study was comparable, whereas the sensitivity was relatively low, which may be the result of the lack of performance of the ultrastaging procedure.…”
Section: Discussionsupporting
confidence: 74%
“…It has been suggested that ICG provides better tissue penetration than the other tracers used, as it may be suggested by our findings, and also makes identification easier for the surgeon [ 33 , 34 ]. In addition, comparing our results with a recent meta-analysis [ 27 ] of patients with low- and intermediate-risk endometrial cancer that used ICG as an SLN tracer, we achieved a higher bilateral rate of SLN mapping with ICG with similar overall detection rates, proving the ICG is a more suitable tracer option. Although this meta-analysis only included the ICG data of the studies included, several of them used multiple tracers and small populations of patients for ICG were used.…”
Section: Discussionsupporting
confidence: 54%
“…Few papers have been published comparing ICG with Tc99m + ICG, but in a study [ 26 ] that compared Tc99m alone vs. ICG + Tc99m, the total bilateral detection rate was 72.1%, without significant differences between ICG as a single tracer and Tc99m + ICG (75% vs. 87.3%, respectively; p = 0.1). In a recent meta-analysis [ 27 ], researchers showed that SLN mapping with ICG has a high overall detection rate of 95.6% (95% CI = 92.4–97.9%) and a bilateral detection rate of 76.5% (95% CI = 68.1–84.0) in low- and intermediate-risk endometrial cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Sentinel lymph node biopsy has been validated as a standard of care in breast cancer, melanoma and gynaecological malignancies [1][2][3]. With regards to endometrial and cervical cancer, the use of ICG uorescence imaging has been extensively investigated and has proven to be a safe, time-e cient and reliable method compared to standard tracers such as the Patent blue and technetium 99m [4].…”
Section: Introductionmentioning
confidence: 99%